High-strength film paper material and preparation method thereof
By using a combined structure of a kraft paper layer, a polyurethane adhesive layer and a polylactic acid-polybutylene adipate composite film layer in the composite film, the shortcomings of the existing composite films in terms of mechanical properties and environmental protection performance are solved, and a composite film with high peel strength and good environmental protection performance is achieved.
Patent Information
- Application Number
- CN202411965682.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing high-strength composite films have shortcomings in terms of mechanical properties and environmental protection properties, and the peel strength is insufficient and limited to their application range.
The combined structure of a kraft paper layer, a polyurethane adhesive layer and a polylactic acid-polybutylene adipate composite film layer is adopted to improve the strength and environmental protection performance of the composite film through the special polyurethane adhesive.
It significantly improves the peel strength and mechanical properties of the composite film, and also has good environmental protection properties, extending its service life.
Smart Images

Figure CN119711245A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging materials, and specifically relates to a high-strength film paper material and a preparation method thereof. Background Art
[0002] Composite film is a polymer material widely used in packaging, printing, electronic products and other fields. As consumers have higher and higher requirements for product quality and packaging, the market demand for composite films continues to increase, and the application prospects are very broad. In the field of packaging, composite films can be used for packaging of various products such as food, medicine, and daily chemicals. With the continuous improvement of environmental awareness, degradable composite films will become an important trend in the future packaging industry. These new composite films can reduce the pollution of plastic waste to the environment, protect the environment, and improve sustainable development.
[0003] CN103538317A discloses a method for preparing a high-strength paper-plastic composite film, and the technical solution uses an adhesive to compound a polyethylene film layer, an aluminum foil layer, a polyester film layer and a kraft paper film layer, thereby significantly improving the tensile strength and heat sealing performance of the composite film. However, the polyethylene film layer, the polyester film layer and the adhesive are all non-degradable materials, which will have a persistent negative impact on the environment after use, thereby limiting the application prospects of the composite film. CN107902258A discloses a fully degradable paper-plastic composite film paper and a preparation process thereof, and the composite film paper is composed of a polylactic acid film layer, an adhesive layer and a paper layer, and by carefully allocating an adhesive, preparing a polylactic acid film, carrying out a machine-made paper-plastic composite and winding and ripening steps, while ensuring that the composite film paper has environmental protection characteristics, its mechanical properties are also enhanced. However, the technical solution does not further study the peel strength of the composite film, thereby limiting the scope of application of the composite film.
[0004] Therefore, there is an urgent need for a high-strength composite membrane with good mechanical properties and environmental protection performance, so as to further expand the application scope of the composite membrane. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, one of the objects of the present invention is to provide a high-strength film paper material having good peel strength and mechanical properties.
[0006] One of the purposes of the present invention is achieved by the following technical solution:
[0007] A high-strength film paper material, comprising, from bottom to top, a kraft paper layer, a polyurethane adhesive layer and a polylactic acid-polybutylene terephthalate adipate composite film layer;
[0008] The polylactic acid-polybutylene terephthalate adipate composite film layer is made of the following raw materials in parts by weight: 50-70 parts of polylactic acid, 30-50 parts of polybutylene terephthalate adipate, 0.8-1.5 parts of titanate coupling agent, 0.2-0.5 parts of 9,10-dihydroxyoctadecanoic acid, and 0.2-0.5 parts of epoxy soybean oil;
[0009] The polyurethane adhesive layer is made of the following raw materials in parts by weight: 50 to 80 parts of linolenic acid-linalool, 15 to 20 parts of polyisocyanate, 11 to 23 parts of hydrophilic agent, 2.5 to 3.5 parts of chain extender, 1 to 2 parts of catalyst, 2.5 to 3.0 parts of triethylamine, and 2.5 to 3.5 parts of silane coupling agent;
[0010] The structure of the linolenic acid-linalool is:
[0011]
[0012] Furthermore, the preparation process of linolenic acid-linalool comprises the following steps:
[0013] (1) Add α-linolenic acid, linalool and p-toluenesulfonic acid to toluene, react at 110-125° C. for 12-16 hours, and prepare intermediate 1 after treatment; the structure of intermediate 1 is:
[0014]
[0015] (2) Add intermediate 1 to dichloromethane, cool to 0°C, then add m-chloroperbenzoic acid in batches, react at 0-10°C for 36-48h after the addition is complete, and prepare intermediate 2 after treatment; the structure of intermediate 2 is:
[0016]
[0017] (3) Add intermediate 2, betaine hydrochloride, and tert-butyl perbenzoate to toluene, react at 110-125° C. for 5-7 hours, and obtain linolenic acid-linalool after treatment.
[0018] Furthermore, in step (1), the molar ratio of α-linolenic acid, linalool and p-toluenesulfonic acid is 1:(1.1-1.5):(0.6-0.75).
[0019] Furthermore, in step (2), the molar ratio of the intermediate 1 to m-chloroperbenzoic acid is 1:(5-6).
[0020] Furthermore, in step (3), the molar ratio of the intermediate 2, betaine hydrochloride, and tert-butyl perbenzoate is 1:(5-6):(15-20).
[0021] Furthermore, the polyisocyanate is one of trimethylhexamethylene diisocyanate (TMDI) and isophorone diisocyanate (IPDI); the hydrophilic agent is one of dimethylolpropionic acid, dimethylolbutyric acid, and 2-hydroxyethyl acrylate; the chain extender is glycerol; the catalyst is dibutyltin dilaurate; and the silane coupling agent is one of (3-glycidoxypropyl)methyldiethoxysilane and (3-glycidoxypropyl)triethoxysilane.
[0022] A second object of the present invention is to provide a method for preparing a high-strength membrane paper material.
[0023] The second object of the present invention is achieved by adopting the following technical solution:
[0024] The method for preparing the above-mentioned high-strength membrane paper material comprises the following steps:
[0025] S1: adding a polylactic acid-polybutylene terephthalate adipate blend into a tape casting machine to prepare the polylactic acid-polybutylene terephthalate adipate composite film layer through a tape casting process;
[0026] The preparation method of the polylactic acid-polybutylene terephthalate adipate blend comprises: mixing lactic acid, polybutylene terephthalate adipate, titanate coupling agent, 9,10-dihydroxyoctadecanoic acid and epoxy soybean oil, and then performing melt extrusion and granulation to obtain the blend;
[0027] S2: adding polyurethane adhesive into the adhesive tank, applying adhesive to the corona surface of the polylactic acid-polybutylene terephthalate adipate composite film layer and drying, so as to form a polyurethane adhesive layer;
[0028] The preparation method of the polyurethane adhesive comprises: mixing linolenic acid-linalool and a hydrophilic agent and stirring them uniformly, then adding a polyisocyanate and a catalyst to carry out a heating reaction, adding a neutralizing agent after the reaction system is cooled to 25-30° C., adding a silane coupling agent after a period of neutralization reaction to continue the reaction, and concentrating the reaction system to obtain the polyurethane adhesive;
[0029] S3: Using a composite roller to press the kraft paper onto the polyurethane adhesive layer, and obtaining the high-strength film paper material after aging.
[0030] Furthermore, in step S2, the drying temperature is 60-90° C., and the time is 1-3 min; the heating reaction temperature is 75-85° C., and the time is 3-4 h; the neutralization reaction time is 25-30 min; and the continued reaction time is 20-30 min.
[0031] Furthermore, the heating temperature of the casting machine in step S1 is 170-180°C.
[0032] Furthermore, in step S3, the temperature of the composite roller is 65-80° C.; the aging temperature is 40-50° C., and the aging time is 60-72 hours.
[0033] Furthermore, the thickness of the polylactic acid-polybutylene terephthalate adipate plastic 1 is 18 μm; the thickness of the polyurethane adhesive 2 is 3 μm; the basis weight of the kraft paper 3 is 65 g / m 2 .
[0034] Furthermore, the corona value is ≥ 45 dynes.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The present invention provides a high-strength film paper material, which is formed by pressing a kraft paper layer and a PLA / PBAT composite film layer with a special polyurethane adhesive. The polyurethane adhesive has excellent adhesion, which helps to improve the strength of the film paper material. The main raw materials of the polyurethane adhesive are linolenic acid-linalool and polyisocyanate. The linolenic acid-linalool structure has a quaternary ammonium salt group, an alcohol hydroxyl group, an ester group and a regular fatty chain. The quaternary ammonium salt group is introduced into the polyurethane adhesive prepared by reacting with the polyisocyanate. The quaternary ammonium salt group can enhance the force between polyurethane molecules, improve the viscosity of the polyurethane adhesive, and then help to improve the peel strength of the composite film; secondly, the ester group introduced into the polyurethane adhesive has a higher cohesive energy, which is also beneficial to improve its peel strength and tensile strength. In addition, the polyurethane adhesive of the present invention also has a relatively obvious antibacterial effect, thereby improving the service life of the film paper material.
[0037] (2) When preparing the polyurethane adhesive, the present invention uses a silane coupling agent to introduce silicon-oxygen bonds into the polyurethane adhesive. In the process of preparing the composite film, the silicon-oxygen bonds will be hydrolyzed into active silicon hydroxyl groups, which will undergo condensation reactions with the active group hydroxyl groups on the surface of the substrate to form chemical bonds, thereby further improving the peel strength of the composite film.
[0038] (3) The raw materials for preparing the polyurethane adhesive of the present invention are linolenic acid and linalool, both of which can be extracted from plants and will not cause secondary pollution during the degradation process of the film paper material, so that the composite film has both excellent mechanical properties and environmental protection properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The schematic diagram of the synthesis of linolenic acid-linalool of the present invention; DETAILED DESCRIPTION
[0040] Below, in conjunction with the accompanying drawings and specific embodiments, the present invention is further described. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.
[0041] (I) Preparation Example
[0042] Preparation Example 1
[0043] A method for preparing linolenic acid-linalool, such as Figure 1 As shown, the following steps are included:
[0044] (1) α-linolenic acid (0.2 mol), linalool (0.22 mol), and p-toluenesulfonic acid monohydrate (0.12 mmol) were added to 500 mL of toluene, stirred evenly at room temperature, and then heated to 115° C. for reaction for 14 h; the reaction solution was cooled to room temperature, diluted with ethyl acetate, and then poured into a saturated sodium bicarbonate aqueous solution to adjust the pH to neutral, the organic phase was separated, and the aqueous phase was extracted twice with ethyl acetate. The organic phases were combined and dried over anhydrous sodium sulfate, concentrated, and purified by distillation to obtain intermediate 1. MS: m / z (%) [M+] calcd for C 28 H 46 O2:415.35;found:415.35.
[0045] (2) Add intermediate 1 (0.2 mol) to 700 mL of dichloromethane, cool to 0°C, then add (1.1 mol) of m-chloroperbenzoic acid in batches, and react at 5°C for 40 h after the addition is complete; the reaction solution is naturally warmed to room temperature and 150 mL of a saturated solution of sodium thiosulfate is added to quench the reaction; after separation, the organic phase is dried over anhydrous sodium sulfate, concentrated, and purified by distillation to obtain intermediate 2. 1 H NMR (C 28 H 46 O7, 400MHz, CDCl3): δ2.93 (m, 1H), 2.60 (m, 1H), 2.35 (m, 9H), 1.66 (m, 1H), 1.66 (m, 2H), 1.51-1.33 (m, 23H), 1.20 (s, 6H), 0.89 (t, 3H).
[0046] (3) Add intermediate 2 (0.1 mol) and betaine hydrochloride (0.55 mol) to 500 mL of toluene, and then add tert-butyl perbenzoate (TBPB, 1.7 mol), and react at 115° C. for 6 h; cool the reaction solution to room temperature, add saturated sodium bicarbonate solution to quench the reaction, take the organic phase, dry it with anhydrous sodium sulfate, concentrate it, and purify it by column chromatography (eluent, acetonitrile: water = 70:30) to obtain linolenic acid-linalool. 1 H NMR (C 53 H 106 C l5 N5O 17 ,400MHz, CDCl3): δ5.40 (s, 3H), 4.58-4.37 (m, 6H), 4.20 (s, 10H), 4.08-3.99 (m, 4H), 3.30 (s, 45H), 2.35 (t, 2H), 1.66-1.25 (m, 27H), 1.14 (s, 6H), 0.89 (t, 3H).MS: m / z (%) [M]calcd for C53H106Cl5N5O17:1084.75; found:1084.73.
[0047] Preparation Example 2
[0048] The preparation process of linolenic acid-linalool comprises the following steps:
[0049] (1) 0.2 mol α-linolenic acid, 0.5 mol linalool, and 0.13 mmol monohydrated p-toluenesulfonic acid were added to 500 mL of toluene, stirred evenly at room temperature, and then heated to 110° C. for 16 h; the reaction solution was cooled to room temperature, diluted with ethyl acetate, and poured into a saturated sodium bicarbonate aqueous solution to adjust the pH to neutral, the organic phase was separated, and the aqueous phase was extracted twice with ethyl acetate, the organic phases were combined, dried with sodium sulfate, concentrated, and purified by distillation to obtain Intermediate 1. The MS results showed that they were consistent with those of Example 1.
[0050] (2) Add intermediate 1 (0.2 mol) to 700 mL of dichloromethane, cool to 0°C, then add (1 mol) of m-chloroperbenzoic acid in batches, and react at 0°C for 48 h after the addition is complete; the reaction solution is naturally warmed to room temperature and 150 mL of a saturated solution of sodium thiosulfate is added to quench the reaction; after separation, the organic phase is taken and dried over anhydrous sodium sulfate, concentrated, and purified by distillation to obtain intermediate 2. 1 The H NMR results were consistent with those of Example 1.
[0051] (3) In 500 mL of toluene, intermediate 2 (0.1 mol) and betaine hydrochloride (0.5 mol) were added, and then tert-butyl perbenzoate (TBPB, 1.5 mol) was added, and the mixture was reacted at 110° C. for 7 h. The reaction solution was cooled to room temperature, and a saturated sodium bicarbonate solution was added to quench the reaction. The organic phase was dried over anhydrous sodium sulfate, concentrated, and purified by column chromatography (eluent, eluent, acetonitrile: water = 70:30) to obtain linolenic acid-linalool. 1 The results of H NMR and MS were consistent with those of Example 1.
[0052] Preparation Example 3
[0053] The preparation process of linolenic acid-linalool comprises the following steps:
[0054] (1) α-linolenic acid (0.2 mol), linalool (0.30 mol), and p-toluenesulfonic acid monohydrate (0.15 mmol) were added to 500 mL of toluene, stirred evenly at room temperature, and then heated to 125° C. for reaction for 12 h; the reaction solution was cooled to room temperature, diluted with ethyl acetate, and poured into a saturated sodium bicarbonate aqueous solution to adjust the pH to neutral, the organic phase was separated, and the aqueous phase was extracted twice with ethyl acetate, the organic phases were combined, dried with sodium sulfate, concentrated, and purified by distillation to obtain Intermediate 1. The MS results showed that they were consistent with those of Example 1.
[0055] (2) Add intermediate 1 (0.2 mol) to 700 mL of dichloromethane, cool to 0°C, then add (1.2 mol) of m-chloroperbenzoic acid in batches, and react at 10°C for 36 h after the addition is complete; the reaction solution is naturally warmed to room temperature and 150 mL of a saturated solution of sodium thiosulfate is added to quench the reaction; after separation, the organic phase is taken and dried over anhydrous sodium sulfate, concentrated, and purified by distillation to obtain intermediate 2. 1 The H NMR results were consistent with those of Example 1.
[0056] (3) In 500 mL of toluene, intermediate 2 (0.1 mol) and betaine hydrochloride (0.6 mol) were added, and then tert-butyl perbenzoate (2 mol) was added, and the mixture was reacted at 125° C. for 5 h. The reaction solution was cooled to room temperature, and a saturated sodium bicarbonate solution was added to quench the reaction. The organic phase was dried over anhydrous sodium sulfate, concentrated, and purified by column chromatography (eluent, eluent, acetonitrile: water = 70:30) to obtain linolenic acid-linalool. 1 The results of H NMR and MS were consistent with those of Example 1.
[0057] (II) Embodiment
[0058] Example 1
[0059] A high-strength film paper material, comprising, from bottom to top, a kraft paper layer, a polyurethane adhesive layer and a polylactic acid-polybutylene terephthalate adipate composite film layer;
[0060] The polylactic acid-polybutylene terephthalate adipate composite film layer is made of the following raw materials in parts by weight: 60 parts of polylactic acid, 40 parts of polybutylene terephthalate adipate, 1 part of titanate coupling agent, 0.3 parts of 9,10-dihydroxyoctadecanoic acid, and 0.3 parts of epoxy soybean oil;
[0061] The polyurethane adhesive layer is made of the following raw materials in parts by weight: 70 parts of linolenic acid-linalool of Preparation Example 1, 18 parts of isophorone diisocyanate, 17 parts of 2-hydroxyethyl acrylate, 3 parts of glycerol, 1.5 parts of dibutyltin dilaurate, 2.8 parts of triethylamine, and 2.8 parts of (3-glycidoxypropyl)triethoxysilane;
[0062] This embodiment also provides a method for preparing the above-mentioned high-strength membrane paper material, comprising the following steps:
[0063] S1: According to the above ratio, polylactic acid, polybutylene terephthalate adipate, titanate coupling agent, 9,10-dihydroxyoctadecanoic acid and epoxy soybean oil are mixed, melted in a twin-screw extruder (the temperatures in the temperature control zone are 40°C, 60°C, 120°C, 140°C, 150°C, 160°C, 165°C and 170°C respectively), and then the obtained material is plasticized and granulated to obtain a polylactic acid-polybutylene terephthalate adipate blend; the polylactic acid-polybutylene terephthalate adipate blend is added to a casting machine and prepared at 175°C by a casting process to obtain the polylactic acid-polybutylene terephthalate adipate composite film layer.
[0064] S2: According to the above ratio, linolenic acid-linalool and 2-hydroxyethyl acrylate were mixed and stirred at room temperature for 0.5h, and then isophorone diisocyanate was added in batches to react for 0.5h, and then dibutyltin dilaurate was added to react at 78°C for 3.5h; the reaction system was cooled to 30°C, and triethylamine was added to neutralize the reaction for 30min, during which an appropriate amount of acetone was added to reduce the viscosity of the reaction system; then, the shear rate was set to 800rpm, and deionized water was slowly added to the prepolymer. After the system phase inversion was stable, (3-glycidoxypropyl)triethoxysilane was added to react for 25min. Finally, the acetone was removed using a rotary evaporator to obtain a polyurethane adhesive. The polyurethane adhesive is added into the adhesive tank, and the corona surface (corona value ≥ 45 dynes) of the polylactic acid-polybutylene terephthalate adipate composite film layer obtained in step (1) is glued and dried at 75° C. for 2 min and 95° C. for 2 min to form a polyurethane adhesive layer.
[0065] S3: Using a composite roller (temperature of 72° C.), press the kraft paper onto the polyurethane adhesive layer formed in step (2), and age it at 45° C. for 65 h to obtain a composite high-strength film-paper material.
[0066] Example 2
[0067] A high-strength film paper material, comprising, from bottom to top, a kraft paper layer, a polyurethane adhesive layer and a polylactic acid-polybutylene terephthalate adipate composite film layer;
[0068] The polylactic acid-polybutylene terephthalate adipate composite film layer is made of the following raw materials in parts by weight: 50 parts of polylactic acid, 30 parts of polybutylene terephthalate adipate, 0.8 parts of titanate coupling agent, 0.2 parts of 9,10-dihydroxyoctadecanoic acid, and 0.2 parts of epoxy soybean oil;
[0069] The polyurethane adhesive layer is made of the following raw materials in parts by weight: 50 parts of linolenic acid-linalool, 15 parts of trimethyl hexamethylene diisocyanate, 11 parts of dimethylol butyric acid, 2.5 parts of glycerol, 1 part of dibutyltin dilaurate, 2.5 parts of triethylamine, and 2.5 parts of (3-glycidoxypropyl)methyldiethoxysilane;
[0070] This embodiment also provides a method for preparing the above-mentioned high-strength membrane paper material, comprising the following steps:
[0071] S1: According to the above ratio, polylactic acid, polybutylene terephthalate adipate, titanate coupling agent, 9,10-dihydroxyoctadecanoic acid and epoxy soybean oil are mixed, melted in a twin-screw extruder (the temperatures in the temperature control zone are 40°C, 60°C, 120°C, 140°C, 150°C, 160°C, 165°C and 170°C respectively), and then the obtained material is plasticized and granulated to obtain a polylactic acid-polybutylene terephthalate adipate blend; the polylactic acid-polybutylene terephthalate adipate blend is added to a casting machine and prepared at 170°C by a casting process to obtain the polylactic acid-polybutylene terephthalate adipate composite film layer.
[0072] S2: According to the above ratio, linolenic acid-linalool and 2-hydroxyethyl acrylate were mixed and stirred at room temperature for 0.5h, and then trimethylhexamethylene diisocyanate was added in batches to react for 0.5h, and then dibutyltin dilaurate was added to react at 75°C for 4h; the reaction system was cooled to 30°C, and triethylamine was added to neutralize and react for 30min. During this period, an appropriate amount of acetone was added to reduce the viscosity of the reaction system; then, the shear rate was set to 900rpm, and deionized water was slowly added to the prepolymer. After the system phase inversion was stable, (3-glycidoxypropyl)methyldiethoxysilane was added to react for 30min. Finally, the acetone was removed by a rotary evaporator to obtain a polyurethane adhesive. Add the polyurethane adhesive into the adhesive tank, apply adhesive to the corona surface (corona value ≥ 45 dynes) of the polylactic acid-polybutylene terephthalate adipate composite film layer obtained in step (1), and dry at 85° C. for 2 min and 95° C. for 2 min to form a polyurethane adhesive layer.
[0073] S3: Using a composite roller (temperature of 65° C.), press the kraft paper onto the polyurethane adhesive layer formed in step (2), and age it at 40° C. for 72 hours to obtain a composite high-strength film-paper material.
[0074] Example 3
[0075] A high-strength film paper material, comprising, from bottom to top, a kraft paper layer, a polyurethane adhesive layer and a polylactic acid-polybutylene terephthalate adipate composite film layer;
[0076] The polylactic acid-polybutylene terephthalate adipate composite film layer is made of the following raw materials in parts by weight: 70 parts of polylactic acid, 50 parts of polybutylene terephthalate adipate, 1.5 parts of titanate coupling agent, 0.5 parts of 9,10-dihydroxyoctadecanoic acid, and 0.5 parts of epoxy soybean oil;
[0077] The polyurethane adhesive layer is made of the following raw materials in parts by weight: 80 parts of linolenic acid-linalool, 20 parts of isophorone diisocyanate, 23 parts of dimethylol propionic acid, 3.5 parts of glycerol, 2 parts of dibutyltin dilaurate, 3 parts of triethylamine, and 3 parts of (3-glycidoxypropyl)triethoxysilane;
[0078] This embodiment also provides a method for preparing the above-mentioned high-strength membrane paper material, comprising the following steps:
[0079] S1: According to the above ratio, polylactic acid, polybutylene terephthalate adipate, titanate coupling agent, 9,10-dihydroxyoctadecanoic acid and epoxy soybean oil are mixed, melted in a twin-screw extruder (the temperatures in the temperature control zone are 40°C, 60°C, 120°C, 140°C, 150°C, 160°C, 165°C and 170°C respectively), and then the obtained material is plasticized and granulated to obtain a polylactic acid-polybutylene terephthalate adipate blend; the polylactic acid-polybutylene terephthalate adipate blend is added to a casting machine and prepared at 180°C by a casting process to obtain the polylactic acid-polybutylene terephthalate adipate composite film layer.
[0080] S2: According to the above ratio, linolenic acid-linalool and 2-hydroxyethyl acrylate were mixed and stirred at room temperature for 0.5h, and then isophorone diisocyanate was added in batches to react for 0.5h, and then dibutyltin dilaurate was added to react at 85°C for 3h; the reaction system was cooled to 30°C, and triethylamine was added for neutralization reaction for 30min, during which an appropriate amount of acetone was added to reduce the viscosity of the reaction system; then, the shear rate was set to 800rpm, and deionized water was slowly added to the prepolymer. After the system phase inversion was stable, (3-glycidoxypropyl) triethoxysilane was added to react for 20min, and finally, the acetone was removed by a rotary evaporator to obtain a polyurethane adhesive. The polyurethane adhesive was added to the adhesive tank, and the corona surface (corona value ≥ 45 dynes) of the polylactic acid-polybutylene adipate composite film layer obtained in step (1) was glued and dried at 65°C for 2min and 95°C for 2min to form a polyurethane adhesive layer.
[0081] S3: Using a composite roller (temperature of 80° C.), press the kraft paper onto the polyurethane adhesive layer formed in step (2), and age it at 50° C. for 60 h to obtain a composite high-strength film-paper material.
[0082] (III) Comparative ratio
[0083] Comparative Example 1
[0084] A film paper material, which differs from Example 1 in that linolenic acid-linalool is replaced by an equal amount of polyether polyol 2000.
[0085] (IV) Test Examples
[0086] Test Example 1
[0087] The film paper materials prepared in Examples 1 to 3 and Comparative Example 1 were subjected to peel force tests, mechanical property tests and barrier property tests, and the test methods were as follows: the peel force was tested according to GB / T 36392-2018 "Laminated paper and paperboard for food packaging"; the tensile strength was tested according to GB / T1040.3-2006 standard, and the test rate was 250 mm / min; the oxygen permeability of each group of film paper materials was determined according to GB / T1038-2000 "Plastic film and sheet gas permeability test method pressure difference method", and the test conditions were 23°C and 0% RH; the water vapor permeability of each group of film paper materials was determined according to the national standard GB / T1037-88 "Plastic film and sheet water vapor permeability test method cup method", and the test conditions were 38°C and 90% RH, as shown in Table 1.
[0088] Table 1 Performance results of the membrane paper materials of Examples 1 to 3 and Comparative Example 1
[0089]
[0090] As shown in Table 1, compared with Comparative Example 1, the film paper materials prepared in Examples 1 to 3 of the present invention have excellent peel strength and tensile properties. The main raw materials of the polyurethane adhesive of the present invention are linolenic acid-linalool and polyisocyanate. The linolenic acid-linalool structure has a quaternary ammonium salt group, an alcohol hydroxyl group, an ester group and a regular fatty chain. The quaternary ammonium salt group is introduced into the polyurethane adhesive prepared by reacting with polyisocyanate. The quaternary ammonium salt group can enhance the interaction between polyurethane molecules and improve the viscosity of the polyurethane adhesive, thereby helping to improve the peel strength of the composite film; secondly, the ester group introduced into the polyurethane adhesive has a higher cohesive energy, which is also conducive to improving its peel strength and tensile strength.
[0091] Test Example 2
[0092] The polyurethane adhesive layers prepared in Examples 1 to 3 and Comparative Example 1 were tested for their antibacterial properties. The test method was as follows: the quaternary ammonium salt aqueous polyurethane adhesive prepared above was slowly cast into a cleaned polytetrafluoroethylene mold, and the bubbles in the dispersion were removed by a vacuum oven. After being placed at room temperature for 1 day, the dispersion was dried in a 45°C oven for 65 hours, and cured under ultraviolet light for 30 seconds to obtain a polyurethane adhesive film sample. The polyurethane adhesive film sample was tested for its antibacterial properties according to QB / T2591-2003, as shown in Table 2.
[0093] Table 2 Antibacterial performance test results of polyurethane adhesives of Examples 1 to 3 and Comparative Example 1
[0094] category Antimicrobial grade Example 1 Level 0 Example 2 Level 0 Example 3 Level 0 Comparative Example 1 >Level 2
[0095] As shown in Table 2, the polyurethane adhesive of the present invention has a relatively obvious antibacterial effect. Compared with the plastic layer and the paper base layer, the adhesive layer is more likely to breed antibacterial bacteria and affect the service life of the paper-plastic composite film. The present invention improves the antibacterial performance of the adhesive and thus improves the service life of the composite film.
[0096] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A high-strength film paper material, characterized in that: The high-strength film paper material comprises, from bottom to top, a kraft paper layer, a polyurethane adhesive layer and a polylactic acid-polybutylene terephthalate adipate composite film layer; The polylactic acid-polybutylene terephthalate adipate composite film layer is made of the following raw materials in parts by weight: 50-70 parts of polylactic acid, 30-50 parts of polybutylene terephthalate adipate, 0.8-1.5 parts of titanate coupling agent, 0.2-0.5 parts of 9,10-dihydroxyoctadecanoic acid, and 0.2-0.5 parts of epoxy soybean oil; The polyurethane adhesive layer is made of the following raw materials in parts by weight: 50 to 80 parts of linolenic acid-linalool, 15 to 20 parts of polyisocyanate, 11 to 23 parts of hydrophilic agent, 2.5 to 3.5 parts of chain extender, 1 to 2 parts of catalyst, 2.5 to 3.0 parts of triethylamine, and 2.5 to 3.5 parts of silane coupling agent; The structure of the linolenic acid-linalool is:
2. The high-strength membrane paper material according to claim 1, characterized in that: The preparation process of linolenic acid-linalool comprises the following steps: (1) Add α-linolenic acid, linalool and p-toluenesulfonic acid to toluene, react at 110-125° C. for 12-16 hours, and prepare intermediate 1 after treatment; the structure of intermediate 1 is: (2) Add intermediate 1 to dichloromethane, cool to 0°C, then add m-chloroperbenzoic acid in batches, react at 0-10°C for 36-48h, and prepare intermediate 2 after treatment; the structure of intermediate 2 is: (3) Add intermediate 2, betaine hydrochloride, and tert-butyl perbenzoate to toluene, react at 110-125° C. for 5-7 hours, and obtain linolenic acid-linalool after treatment.
3. The high-strength membrane paper material according to claim 2, characterized in that: The molar ratio of α-linolenic acid, linalool and p-toluenesulfonic acid in step (1) is 1:(1.1-1.5):(0.6-0.75).
4. The high-strength membrane paper material according to claim 2, characterized in that: In step (2), the molar ratio of the intermediate 1 to m-chloroperbenzoic acid is 1:(5-6).
5. The high-strength membrane paper material according to claim 2, characterized in that: In step (3), the molar ratio of the intermediate 2, betaine hydrochloride and tert-butyl perbenzoate is 1:(5-6):(15-20).
6. The high-strength membrane paper material according to claim 1, characterized in that: The polyisocyanate is one of trimethylhexamethylene diisocyanate and isophorone diisocyanate; the hydrophilic agent is one of dimethylolpropionic acid, dimethylolbutyric acid, and 2-hydroxyethyl acrylate; the chain extender is glycerol; the catalyst is dibutyltin dilaurate; and the silane coupling agent is one of (3-glycidoxypropyl)methyldiethoxysilane and (3-glycidoxypropyl)triethoxysilane.
7. The method for preparing a high-strength membrane paper material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: adding a polylactic acid-polybutylene terephthalate adipate blend into a casting machine to prepare the polylactic acid-polybutylene terephthalate adipate composite film layer through a casting process; The preparation method of the polylactic acid-polybutylene terephthalate adipate blend comprises: mixing lactic acid, polybutylene terephthalate adipate, titanate coupling agent, 9,10-dihydroxyoctadecanoic acid and epoxy soybean oil, and then performing melt extrusion and granulation to obtain the blend; S2: adding polyurethane adhesive into the adhesive tank, applying adhesive to the corona surface of the polylactic acid-polybutylene terephthalate adipate composite film layer and drying, so as to form a polyurethane adhesive layer; The preparation method of the polyurethane adhesive comprises: mixing linolenic acid-linalool and a hydrophilic agent and stirring them uniformly, then adding a polyisocyanate and a catalyst to carry out a heating reaction, adding a neutralizing agent after the reaction system is cooled to 25-30° C., adding a silane coupling agent after a period of neutralization reaction to continue the reaction, and concentrating the reaction system to obtain the polyurethane adhesive; S3: Using a composite roller to press the kraft paper onto the polyurethane adhesive layer, and obtaining the high-strength film paper material after aging.
8. The method for preparing a high-strength membrane paper material according to claim 7, characterized in that: In step S2, the drying temperature is 60-90° C. and the time is 1-3 min; the heating reaction temperature is 75-85° C. and the time is 3-4 h; the neutralization reaction time is 25-30 min; and the continued reaction time is 45-60 min.
9. The method for preparing a high-strength membrane paper material according to claim 7, characterized in that: The heating temperature of the casting machine in step S1 is 170-180°C.
10. The method for preparing a high-strength membrane paper material according to claim 7, characterized in that: In step S3, the temperature of the composite roller is 65-80° C.; the aging temperature is 40-50° C., and the aging time is 60-72 hours.
Citation Information
Patent Citations
High-strength paper-plastic composite membrane
CN103538317A
Full-degradable paper-plastic composite film paper and preparation method thereof
CN107902258A
Environment-friendly thermal-insulation plastic film and preparation process thereof
CN109553945A
Biodegradable paper-plastic composite film as well as preparation method and application thereof
CN115892736A
Antibacterial adhesive tape and preparation method thereof
CN115975540A